Exploring the Ethics of Clinical Research in an Urban Community - Grady, Christine (© American Journal of Public Health 2006, 2006)
Objectives. We consulted with representatives of an urban community in Washington, DC, about the ethics of clinical research involving residents of the community with limited access to health care. Methods. A semistructured community consultation was conducted with core members of the Health Partnership Program of the National Institute of Arthritis and Musculoskeletal and Skin Diseases. Three research case examples were discussed; questions and probes (a predetermined question or series of questions used to further investigate or follow-up a response) guided the discussion. Results. The community representatives who took part in the consultation were supportive of research and appreciated the opportunity to be heard. They noted the importance of respecting the circumstances, values, needs, and welfare of research participants; supported widely representative recruitment strategies; and cited the positive benefits of providing care or treatment to participants. Monitoring participants’ welfare and ensuring care at a study’s end were emphasized. Trust was a central theme; participants suggested several trust-enhancing strategies, including full disclosure of information and the involvement of advocates, physicians, and trusted church members. Conclusions. Several important strategies emerged for conducting ethical research in urban communities whose residents have limited access to health care.